Humpback whale song complexity and evolution on a North-western Pacific breeding ground: Okinawa, Japan - Marwood, Eleanor M.; Eichenberger, Franca; Kobayashi, Nozomi; Okabe, Haruna; Ozawa, Sachie; Rendell, Luke Edward; Garland, Ellen Clare (Royal Society Open Science, 2025)
Funding: Royal Society (UF160081, URF\R\221020). Male humpback whales (Megaptera novaeangliae) sing a slowly evolving, sexually selected song display socially learned from conspecifics. Within an ocean basin, song similarity between breeding populations can reveal the degree of connectivity among them. In the northwestern Pacific Ocean, there is a paucity of information on song dynamics and linkages across the ocean basin. Here, we quantified fine-scale song evolution in whales near Okinawa, Japan, using similarity indices (Levenshtein distance and Dice’s similarity) and song complexity measures to investigate three consecutive years (2011–2013) of song dynamics on this breeding ground. Matched song themes revealed minimal evolution between 2011 and 2012, while the 2013 song was more distinct, as singers sang both new and evolved versions of themes. This was mirrored by the song complexity scores, which decreased and then increased over time. Qualitative comparisons of Okinawa song themes to other published North Pacific breeding ground songs revealed many themes were shared across the North Pacific, contributing to the growing body of evidence of a single panmictic song lineage across the North Pacific Ocean basin, in contrast to the South Pacific. Understanding geographically differing song dynamics is essential to revealing the underlying drivers of this ocean basin-wide non-human culture. Peer reviewed